DIFFERENCES OF INDIVIDUAL DEMOGRAPHIC CHARACTERISTICS TOWARDS E-WALLET PAYMENT IN RESTAURANTS - Caroline, Shinta; Putri, Anggraini; Oei, Edy; Verawati, Verawati; Isnovian, Isnovian (UI Scholars Hub, 2021)
Manuscript type: Research paper. Research Aims: This study aims to understand the influence of individual differences to customers’ intention to use e-wallet as a method of payment at café or snack bar, fast food restaurant, and food court. Design/methodology/approach: A total of 481 valid online questionnaires were collected from DKI Jakarta, Banten and West Java respondents who have paid with e-wallet in restaurants within the last 12 months. SPSS Analysis through ANOVA with Dunnet’s C post hoc analysis was used to analyse the differences between groups. Research Findings: Individual differences such as gender, income and education have significant influence in customers’ intention to use e-wallet as a method of payment in restaurants. However, unlike previous studies, age does not have a significant impact on e-wallet adoption at restaurants. This study also demonstrated that type of restaurant makes significant influence for customers’ intention to use e-wallet. Originality: There has been a study about individual differences that influence adoption of NFC for payment in the US. However, this is the first study in Indonesia to understand how individual differences significantly influence e-wallet adoption for payment methods in restaurants. Practitioner Implication: This study provides insight for restaurants and e-wallet providers about consumer behaviour and develop marketing plans. Research limitation/Implications: This study was limited to some restaurant types and only towards respondents who have used e-wallet in restaurants within the last 12 months. Further research could be conducted in other types of restaurants and non-digital savvy respondents.